2020
DOI: 10.3390/f11010109
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Land Use/Cover Change on Ecosystem Service Values in the Kilombero Valley Floodplain, Southeastern Tanzania

Abstract: Land use/cover change (LUCC) attributed to natural factors and human activities has led to the loss of ecosystem services, making the quantitative valuation of ecosystem services the scientific focal pointfor sustainable development. This study assessed changes in the ecosystem services values (ESVs) due to LUCC during the period 1990–2016 in the Kilombero Valley floodplain, located in southeastern Tanzania. Moderate resolution Landsat images from 1990, 2010 and 2016 were obtained and analyzed using a random f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 33 publications
(102 reference statements)
3
39
1
Order By: Relevance
“…Optimizing land-use structure and protecting natural ecosystems will help increase the ESV. Ecological protection projects are critical to increase the ESV [23]. In this study, deforestation has been shown to have a gigantic impact on the ESV, during 1992-1995, the forestland decreased by 38782.36 hm 2 and ESV decreased by 14.36 × 10 8 yuan.…”
Section: Effects Of Lulc Changes On Esvmentioning
confidence: 65%
“…Optimizing land-use structure and protecting natural ecosystems will help increase the ESV. Ecological protection projects are critical to increase the ESV [23]. In this study, deforestation has been shown to have a gigantic impact on the ESV, during 1992-1995, the forestland decreased by 38782.36 hm 2 and ESV decreased by 14.36 × 10 8 yuan.…”
Section: Effects Of Lulc Changes On Esvmentioning
confidence: 65%
“…Our LULC maps are integral part of it, and continuous monitoring may support those efforts [20]. LULC often results in extensive loss of ecosystem services [23,109]. Hence, our LULC change assessment may serve to quantifying related ecosystem services.…”
Section: Lulc Changementioning
confidence: 99%
“…Catchment-wide studies are rare, in particular in East Africa. LULC change in the Kilombero valley was addressed in several case studies [6,12,[17][18][19][20][21][22][23][24][25][26]. Only a few of these studies explored the whole catchment and only few provided an exhaustive evaluation of the generated LULC change maps.…”
Section: Introductionmentioning
confidence: 99%
“…One is based on primary data, the ecological processes and functions that constitute ES are quantified by the ecological model, and then evaluates the economic values of ES. Such a method is performed on one or a few kinds of services rather than the comprehensive ESVs [19][20][21]. The other is the equivalent coefficient method, where ESVs are estimated based on the equivalent coefficient of various ecosystem services and combined with the unit area of the ecosystem [16,22,23].…”
Section: Introductionmentioning
confidence: 99%